(untitled) (Confluenţe Bibliologice, 2025)
The Scientific Library of USARB performs the functions of the Librarianship Center for school libraries, high schools and vocational schools in 15 districts and the municipality of Balti in northern Moldova. The Librarianship Center Center collects, analyzes and synthesizes statistics on school libraries every year. The library’s activity is presented by the methodologists of the educational departments. This article analyzes statistical data for 2013 from the 1293 libraries that own a collection of 10,920,473 documents. 373,735 users borrowed 8,661,966 volumes and accessed 297 workstations.